Strategic Leadership as a Catalyst For Organizational Culture Transformation in Sarawak’s TVET Institutions - Cliffton, Julia; Awang, Marinah; Mansor, Mahaliza (Management Research Journal, 2024)
This study aims to examine the relationship between Strategic Leadership and Organizational Culture transformation in Sarawak’s TVET institutions, recognizing its critical role in ensuring institutional adaptability and long-term sustainability. The research specifically examines the correlation between Strategic Leadership and various dimensions of a Learning Organization, emphasizing its impact on fostering a responsive and innovative organizational culture in vocational education. A quantitative correlational research design was adopted, involving 150 teachers from three vocational colleges in Sarawak. Data were collected using a questionnaire and analyzed through Pearson’s correlation analysis. The findings reveal a strong positive correlation (r = .72, p < .001) between Strategic Leadership and Organizational Culture transformation, highlighting that institutions with effective strategic leadership exhibit higher adaptability, improved collaboration, and a stronger learning-oriented culture. The study concludes that Strategic Leadership is a key driver in navigating institutional challenges, fostering continuous improvement, and ensuring TVET institutions remain aligned with evolving industry needs. The results provide valuable insights for policymakers, institutional leaders, and educators on the importance of leadership in cultivating an agile and progressive learning environment. These findings reinforce the need to integrate strategic leadership practices into TVET governance and professional development programs, ensuring the future sustainability and competitiveness of vocational education in Sarawak.